Global Change, Clonal Growth, and Biological Invasions by Plants - Peter Alpert (Frontiers Research Topics, 2016)
There are few more active frontiers in plant science than helping understand and predict the ecological consequences of on-going, global changes in climate, land use and cover, nutrient cycling, and acidity. This collection of research papers and reviews focuses on how these changes are likely to interact with two important factors, clonal growth in plants and the introduction of species into new regions by humans, to reshape the ecology of our world. Clonal growth is vegetative reproduction in which offspring remain attached to the parent at least until establishment. Clonal growth is associated with the invasiveness of introduced species, their tendency to spread after introduction and negatively affect other species. Will changes in climate, land cover, or nutrients further increase biological invasions by introduced, clonal plants? The articles in this book seek to address this question with new research and theory on clonal growth and its interactions with invasiveness and other components of global change.